APTAMER: A REVIEW ON IT’S IN VITRO SELECTION AND DRUG DELIVERY SYSTEM - KUMAR, VINOD; RAJ S., BRITO; KANAKARAJ, LAKSHMI; PAUL A., DEEVAN; K., KAVITHA; M., RAVI; P., SUCHARITHA (International Journal of Applied Pharmaceutics, 2022)
In recent year, Aptamer has been one of the key tools in the field of advanced drug delivery systems. Aptamer are oligonucleotides or peptides that bind to a specific target molecule. In this review we summarize the major differences between the antibody and an Aptamer along with the different methodology of the In vitro selection of the Aptamer by using SELEX (Systematic evolution of ligands by exponential enrichment) technique. SELEX is a technique which has a based biosensor and some of the novel drug delivery system. The article referred in this review was referred from the above said source was in the range of 1990-2020 y. Primary contents is searched from science direct, springer nature, scopus indexed journals. The resources are downloaded from google scholar, peer-reviewed published literature from scientific journals and books.